TNF-α inhibitors as therapy for drug-induced severe cutaneous adverse reactions: a case series - Yanjun Chu; Mengjun Xu; Xiaoqing Dong; Jiong Zhou (Taylor & Francis Group, 2024)
Background: Severe cutaneous adverse reactions (SCARs) including acute generalized exanthematous pustulosis (AGEP), drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens-Johnson syndrome (SJS) and its related diseases, and toxic epidermal necrolysis (TEN) are of great concern due to their high mortality rates. While systemic corticosteroids have been widely used to treat SCARs, their efficacy has been debated due to the increased risk of infection. In recent years, tumor necrosis factor (TNF)-α inhibitors have emerged as a new therapeutic option.Objectives: This study aimed to report the clinical outcomes of different types of SCARs treated with TNF-α inhibitors.Methods: Since 2020, our department has treated 4 SCAR patients, aged 20-54 years, with 1 diagnosed with AGEP and 3 with TEN. All patients received TNF-α inhibitor therapy, including etanercept and adalimumab.Results: All 4 patients achieved successful outcomes, with rapid recovery of skin lesions and mucosal involvement, and no subsequent complications. Notably, one patient improved after initial corticosteroid and intravenous immunoglobulin treatment failed.Discussion: The pathogenesis of SCARs involves T cell-mediated keratinocyte apoptosis, in which TNF-α plays a crucial role. TNF-α inhibitors, by downregulating the TNF-α signaling pathway, have demonstrated potential in the treatment of SCARs. However, large-scale clinical trials supporting their efficacy are still lacking, and their use remains limited, requiring a careful balance of treatment risks and benefits.